2021
DOI: 10.1111/iwj.13651
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic foot ulcer, the effect of resource‐poor environments on healing time and direct cost: A cohort study during Syrian crisis

Abstract: Diabetic foot ulcer (DFU) is one of the slowest healing wounds that hurt the human body. Many studies from developed countries are concerned about materials, procedures, and equipment that accelerate the healing time. In Sweden, the diabetic foot management costs around 24965$/patient. In this review, we would evaluate the healing time of DFUs during what is considered one of the worst humanitarian crisis of the 21st century. 1747 DFUs were studied from the main diabetic foot clinic in Damascus (2014‐2019). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…This study included both male and female patients, with a male-to-female ratio of around 3:1. Other studies have also observed that men were at a higher risk of developing foot ulceration in comparison to females [ 11 , 12 ]. The mean age at presentation in our study population was 51 years and majority of patients fell in the age group of 50-59 years.…”
Section: Discussionmentioning
confidence: 95%
“…This study included both male and female patients, with a male-to-female ratio of around 3:1. Other studies have also observed that men were at a higher risk of developing foot ulceration in comparison to females [ 11 , 12 ]. The mean age at presentation in our study population was 51 years and majority of patients fell in the age group of 50-59 years.…”
Section: Discussionmentioning
confidence: 95%
“…15 A SINBAD score <3 is associated with a healing rate of 60% at 12 weeks compared with 35% if the score is > 3, and a risk of MajA at 6 months of 2.7% versus 0.7%. 23 A 2021 study 27 28 Two recent studies found that a high SINBAD score was associated with the presence of DFU infection with extended-spectrum beta-lactamase (ESBL)-producing bacteria 29 or Meti-R Staph aureus. 30 In 2019, the IWGDF issued a strong recommendation to use the SINBAD system for communications among health professionals on the characteristics of a foot ulcer in a person with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Alasabeck et al. showed a median healing time of 14 weeks in patients with a SINBAD score ≥3 and 4 weeks in patients with a SINBAD score ≤ 2 28 …”
Section: Discussionmentioning
confidence: 99%
“…This is supported by several studies that suggest the ability of a classification system (eg, SINBAD) to predict future performance outcomes is dependent on external factors and internal validity 41–43 . Alsabek and Abdul Aziz 44 expanded on this to suggest that resource-poor environments can delay access to immediate DFU assessment and classification, therefore increasing the likelihood of lower-limb amputation.…”
Section: Validitymentioning
confidence: 91%